Ekplorasi Penghambat Kemampuan Membaca pada Siswa Kelas 1 SDN I Selong Lombok Timur - Mohammad Irfan; Muh. Jaelani Al-Pansori; Muh. Taufiq (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This study aims to analyze the difficulties of early reading in elementary school students. The type of research used in this study is descriptive research. The subjects of this study were early reading in elementary school students. The data collection methods used were observation, interviews, questionnaires, and documentation. The instrument used was a non-test instrument in the form of a questionnaire regarding early reading. The data obtained were analyzed using qualitative descriptive statistical data analysis techniques. The results of the study that have been described are the difficulties of early reading in elementary school students, lack of interest in learning to read and lack of guidance, difficulties of early reading in elementary school students, namely not being able to recognize letters, not being able to read syllables, not being able to read words, and not being able to arrange the arrangement of letters in spelling words. The conclusion of this study is that the difficulties of early reading are due to the lack of interest in learning students, lack of interest in reading, lack of tutoring and lack of family assistance in the process of learning to read early. The implications of implementing this research are to motivate students to learn to understand the content and meaning of a reading, and to motivate students to learn to communicate orally and in writing.